TOXIC WORKPLACE CULTURE, PSYCHOLOGICAL DISTRESS, AND TURNOVER INTENTION AMONG TEACHERS: A MODERATED MEDIATION STUDY (International scientific-electronic journal “Pioneering studies and theories”, 2026)
Workplace culture plays a critical role in shaping not only organizational effectiveness but also the psychological well-being and professional trajectories of employees. Within educational institutions, teachers operate in emotionally demanding environments characterized by continuous interpersonal interaction, high expectations, and complex organizational structures. In such contexts, the presence of toxic workplace culture - manifested through negative leadership practices, interpersonal conflict, lack of support, and organizational injustice - can significantly exacerbate psychological distress and influence employees’ intentions to leave their positions. This study investigates the interrelationship between toxic workplace culture, psychological distress, and turnover intention among teachers, with particular attention to the moderating roles of compensation and institutional context. Drawing upon occupational stress theories and social exchange theories, the research conceptualizes workplace toxicity as a critical job demand that undermines well-being and disrupts reciprocal organizational relationships. The study further explores how variations in salary structures and differences between public and private educational institutions shape employees’ perceptions and responses to adverse work environments. By employing survey-based quantitative design, this research aims to identify the mechanisms through which toxic organizational conditions translate into withdrawal cognitions, including intentions to quit. The findings are expected to contribute to the broader discourse on teacher retention by demonstrating that psychological distress serves as a key mediating factor, while compensation and institutional support may function as partial buffers. Ultimately, the study underscores the importance of fostering supportive, equitable, and psychologically safe workplace environments to enhance teacher well-being, reduce turnover, and sustain long-term professional engagement in the education sector